Microplate-Based Characterization of Protein-Phosphoinositide Binding Interactions Using a Synthetic Biotinylated Headgroup Analogue - Gong, Denghuang (2009)
Membrane lipids act as important regulators of a litany of important physiological and pathophysiological events. Many of them act as site-specific ligands for cytosolic proteins in binding events that recruit receptors to the cell surface and control both protein function and subcellular localization. Phosphatidylinositol phosphates (PIP(n)s) are a family of signaling lipids that regulate numerous cellular processes by interacting with a myriad of protein binding modules. Characterization of PIP(n)-binding proteins has been hampered by the lack of a rapid and convenient quantitative assay. Herein, microplate-based detection is presented as an effective approach to characterizing protein-PIP(n) binding interactions at the molecular level. With this assay, the binding of proteins to isolated PIP(n) headgroups is detected with high sensitivity using a platform that is amenable to high-throughput screening. In the studies described herein, biotinylated PI-(4,5)-P(2) headgroup analogue 1 was designed, synthesized and immobilized onto 96-well streptavidin-coated microplates to study receptor binding. This assay was used to characterize the binding of the PH domain of β-spectrin to this headgroup. The high affinity interaction that was detected for surface association (K(d, surf) = 6 nM ±3), demonstrates that receptor binding modules can form high affinity interactions with lipid headgroups outside of a membrane environment. The results also indicate the feasibility of the assay for rapid characterization of PIP(n)-binding proteins as well as the promise for high-throughput analysis of protein-PIP(n) binding interactions. Finally, this assay was also employed to characterize the inhibition of the binding of receptors to the PIP(n)-derivatized microplates using solution phase competitors. This showcases the viability of this assay for rapid screening of inhibitors of PIP(n)-binding proteins.